2009
DOI: 10.1007/s11010-009-0257-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance due to lipid-induced signaling defects could be prevented by mahanine

Abstract: It is well known that free fatty acids (FFAs) play a key role in implementing insulin resistance and type 2 diabetes. Resources of chemical compounds that intervene the derogatory effect of FFAs are indeed very limited. We have isolated mahanine, a carbazole alkaloid, from the leaves of Murraya koenegii that prevented palmitate-induced inhibition of insulin-stimulated phosphorylation of IRbeta, PI3K, PDK1, and Akt in L6 myotubes. This was also reflected in the palmitate-induced inhibition of insulin-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It is suggested that, in WT mice, saturation of lipid metabolism resulting from excess dietary fat intake inhibits cellular glucose uptake and insulin signaling in peripheral tissues ( e.g. , liver, skeletal muscle, adipose), leading to insulin resistance and compensatory increase in insulin secretion (Biswas et al, 2010). Due to intrinsic defects in lipid metabolism in Gclm(−/−) mice, such a cascade of events may not occur, which may explain the sustained insulin sensitivity in HFD-fed Gclm(−/−) mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that, in WT mice, saturation of lipid metabolism resulting from excess dietary fat intake inhibits cellular glucose uptake and insulin signaling in peripheral tissues ( e.g. , liver, skeletal muscle, adipose), leading to insulin resistance and compensatory increase in insulin secretion (Biswas et al, 2010). Due to intrinsic defects in lipid metabolism in Gclm(−/−) mice, such a cascade of events may not occur, which may explain the sustained insulin sensitivity in HFD-fed Gclm(−/−) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Few isolated pure compounds from the MK leaf have been studied thoroughly for their details signal cross talk mechanism in different disease models including cancer 6 . For example, mahanine, a carbazole alkaloid isolated from MK leaves established its ability to combat against diabetes and the different types of cancer 7 , 8 . In a recent review 9 , we discussed in details the molecular mechanistic insight of the mahanine in different cancer model.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves are a major part of Indian culinary practices with characteristics such as slight pungent odor with bitter taste regularly used for seasoning dishes [19]. Mostly roots, bark and leaves are having active bio-ingredients having antidiabetic [20], anticancer [21], antioxidant [22], hepatoprotective [23], and antilipase activities [24]. Reported important constituents are carbazole alkaloids, coumarins and flavonoids [25].…”
Section: Introductionmentioning
confidence: 99%